2014
DOI: 10.1002/aic.14425
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of oxygen in the segregation of sodium at the surface of molybdenum coated soda‐lime glass

Abstract: Molybdenum (Mo) coated soda‐lime glass is a commonly used substrate for Cu(InGa)Se2 solar cells as it also acts as the sodium (Na) source, which improves the efficiency of these devices. In this work, we investigate how oxygen controls the segregation and accumulation of Na on the Mo surface. A direct relationship between the concentration of surface oxygen and the amount of Na accumulation is showed. Values for the surface segregation ratio and grain boundary diffusion coefficient for Na in Mo are obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…In two publications, Blosch et al [106,107] have stated that Na easily diffuses from internal interfaces of two MoNa layers possibly because Na moves through grain boundaries. In addition they also found that the microstructure of the MoNa layers strongly influence this diffusion, in accordance with several findings [57,108]. Therefore, Blosch et al introduced multi-stacked layers of MoNa to allow more Na to be released and to arrive to the CIGSe layer.…”
Section: Mona Back Contact Layersupporting
confidence: 55%
See 3 more Smart Citations
“…In two publications, Blosch et al [106,107] have stated that Na easily diffuses from internal interfaces of two MoNa layers possibly because Na moves through grain boundaries. In addition they also found that the microstructure of the MoNa layers strongly influence this diffusion, in accordance with several findings [57,108]. Therefore, Blosch et al introduced multi-stacked layers of MoNa to allow more Na to be released and to arrive to the CIGSe layer.…”
Section: Mona Back Contact Layersupporting
confidence: 55%
“…However, also here contradictory results have been presented in the literature, stating that SLG provides an optimal amount of Na [16], that it provides too much Na [97], and that it provides too little Na [34]. The reason for this inconsistency is likely associated with the complexity of the Na out-diffusion process, originating from the glass and going through the Mo layer [57]. A schematic representation of the diffusion process based on the H þ /Na þ ion exchange model is shown in Fig.…”
Section: Soda-lime Glassmentioning
confidence: 62%
See 2 more Smart Citations
“…Heating in air drives Na out of the film where it accumulates on the surface. The presence of oxygen has shown to greatly increase the rate of Na diffusion, 25,26 so the presence of air during the heat treatment facilitates the accumulation of Na on the surface. The newly accumulated Na is once again rinsed away so that the combination of surface accumulation followed by dissolution lowers the Na concentration in the film, making it possible to control Na content by increasing the number of heat/rinse cycles.…”
Section: B Control Of Na Concentration Within Filmsmentioning
confidence: 99%